Tunable band gap and coercivity of bismuth ferrite-polyaniline core-shell nanoparticles: the role of shell thickness - Chaturvedi, Smita; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha (RSC Advances, 2015)
We report a tunable band gap of bismuth ferrite-polyaniline core-shell nanoparticles from 2.24 to 1.98 eV and the variation of coercivity from 118 to 100 Oe, by varying the thickness of the polyaniline shell. Bismuth ferrite nanoparticles were synthesized via a chemical route and coating of polyaniline was achieved by a double surfactant layer technique. Coating of polyaniline introduced oxygen vacancies, local distortions and microstrains in the bismuth ferrite lattice which resulted in a change in the Fe-O-Fe bond angle of the bismuth ferrite lattice. This is confirmed with structural analysis tools i.e. X-ray Diffraction, Fourier Transform Infrared Spectroscopy and Raman spectroscopy. Moreover, the absorption of light around 600 nm is increased and photoluminescence emission around 430 nm is decreased, as the thickness of shell is increased, which also indicates the changes in optical properties due to variation in shell thickness. Thus tunability of the band gap and coercivity is achieved as a function of shell thickness in bismuth ferrite-polyaniline core-shell nanoparticles.